Contributing factors in the prolonged effect of botulinum toxin (Research, Society and Development, 2024)
Botulinum enzyme, more commonly referred to as botulinum toxin or Botox (BT), is a neurotoxin derived from Gram-positive bacteria. The effectiveness of botulinum toxin can vary from person to person and depends on the dose administered, the application technique and the indication for which it is being used. With this in mind, this study aims to investigate the factors contributing to the prolonged effect of botulinum toxin, by means of an integrative review. This is an integrative bibliographic review, which aims to explore and synthesize an analysis of the use of botulinum enzyme and the contributing effects of prolonged action in the aesthetic area, by searching for the most representative published studies on the subject in question. After inclusion and exclusion criteria, 15 manuscripts were selected for presentation and discussion of the results, as they responded to the objectives. Most of the samples came from Medline/PubMed with 67% of the searches, followed by Scielo with 27%, 65% of which used clinical trials with a qualitative approach. Clinical studies have shown that botulinum toxin type A can be effective in reducing the frequency and intensity of migraine attacks in patients with chronic migraine. However, not all patients respond in the same way, and the benefits may vary. In addition, it is important to discuss potential adverse reactions and specific considerations with a healthcare professional before opting for this treatment. However, the application of botulinum toxin can bring with it some side effects resulting from the injection or the product.